Security Challenges in Quantum Key Distribution and Robust Cryptographic Methods for Wireless Body Sensor Networks: A Comprehensive Survey - Gomathy, K.; Mohanasathiya, K. S.; Gomathy, K. (Journal of Neonatal Surgery, 2025)
Wireless Body Sensor Networks (WBSNs) and Quantum Key Distribution (QKD) provide distinct yet interrelated possibilities and challenges in the quickly changing field of network safety. This review explores the safety concerns that come with quantum key distribution (QKD), emphasizing problems like quantum surveillance, protocol weaknesses, and the necessity of workable application solutions. Simultaneously, it examines the strong cryptographic techniques necessary to protect Wireless Body Sensor Networks, which are becoming increasingly important in applications related to individual tracking and medicine. Everyone investigates new approaches, assesses their efficacy, and suggests future lines of inquiry to tackle the critical safety concerns of body networked sensors and quantum messaging. By strengthening the security architecture in both domains, this integrated strategy seeks to provide reliable and solid interaction networks against ever-changing threats.